2008
DOI: 10.1103/physrevb.77.245105
|View full text |Cite
|
Sign up to set email alerts
|

Fulde-Ferrell-Larkin-Ovchinnikov pairing in one-dimensional optical lattices

Abstract: Spin-polarized attractive Fermi gases in one-dimensional (1D) optical lattices are expected to be remarkably good candidates for the observation of the Fulde-Ferrell-Larkin-Ovchinnikov (FFLO) phase. We model these systems with an attractive Hubbard model with population imbalance. By means of the density-matrix renormalization-group method, we compute the pairing correlations as well as the static spin and charge structure factors in the whole range from weak to strong coupling. We demonstrate that pairing cor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(105 citation statements)
references
References 85 publications
(61 reference statements)
8
96
0
1
Order By: Relevance
“…Refs. [48,83]. Moreover, the number n peak of peaks turns out to increase proportionally to ℓ as suggested by the phase term in Eq.…”
Section: Interactionsmentioning
confidence: 78%
“…Refs. [48,83]. Moreover, the number n peak of peaks turns out to increase proportionally to ℓ as suggested by the phase term in Eq.…”
Section: Interactionsmentioning
confidence: 78%
“…In the limit of L → ∞, the density and spin profiles will become flat, while the modulations can then be detected in the respective correlation functions (compare Refs. [33,68] for the attractive Hubbard model). In the experimentally relevant situation of harmonically trapped particles, however, the density profiles themselves should have properties similar to those discussed here for finite systems with open boundary conditions, at least in parts of the particle cloud.…”
Section: Natural Orbitalsmentioning
confidence: 99%
“…Only recently, it was rigorously shown that the partially polarized phase is the onedimensional analogue of the FFLO state by means of exact numerical methods [49,51,[58][59][60], confirming predictions from mean-field theory [61,62] and bosonization [63]. In 1D, this means that the pair-pair correlation functions are modulated with Q = k F ↑ − k F ↓ and decay as a power law, slower than any competing correlation in the two-particle channel (k F σ = πn σ is the Fermi momentum).…”
Section: A Overview: Population-and Mass-imbalanced 1d Mixturesmentioning
confidence: 99%